2011
DOI: 10.4103/0019-5545.75558
|View full text |Cite
|
Sign up to set email alerts
|

Problem-solving counseling as a therapeutic tool on youth suicidal behavior in the suburban population in Sri Lanka

Abstract: Background:Suicidal behaviour among youth is a major public health concern in Sri Lanka. Prevention of youth suicides using effective, feasible and culturally acceptable methods is invaluable in this regard, however research in this area is grossly lacking.Objective:This study aimed at determining the effectiveness of problem solving counselling as a therapeutic intervention in prevention of youth suicidal behaviour in Sri Lanka.Setting and design:This control trial study was based on hospital admissions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The majority employed a pre-test/post-case series study design (k = 11; 57·9%) [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83]. Sixteen (84·2%) recruited participants from community mental health services or hospitals, including inpatient and emergency department settings [73], [74], [75], [76], [77], [78], [79], [80], [83], [84], [85], [86], [87], [88], [89], [90], [91]. Interventions included DBT, CBT, and brief contact interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority employed a pre-test/post-case series study design (k = 11; 57·9%) [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83]. Sixteen (84·2%) recruited participants from community mental health services or hospitals, including inpatient and emergency department settings [73], [74], [75], [76], [77], [78], [79], [80], [83], [84], [85], [86], [87], [88], [89], [90], [91]. Interventions included DBT, CBT, and brief contact interventions.…”
Section: Resultsmentioning
confidence: 99%
“…One study tested a brief contact intervention and reported no between-group differences [85]. A study of a problem solving intervention reported a reduction in the proportion of participants reporting suicide attempts in the treatment group compared to controls [87]. Finally, a study testing an intervention for American Indians reported reductions in suicidal ideation over time [82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a psychiatric diagnosis are at an increased risk of a repeat self-harm and appropriate management of mental illness is the cornerstone of any suicide prevention efforts. [22] Psychological therapies like problem solving therapy[23] and cognitive behavior therapy[23] have been found to be useful in reducing repetition rates of deliberate self-harm. The importance of psychological therapies is obtaining more recognition, but funding and recruitment issues continue to be major hurdles.…”
Section: Discussionmentioning
confidence: 99%
“…Published interventional research for prevention of non-fatal self-poisoning in the Sri Lankan context is limited. One study conducted among young people in an urban population in Sri Lanka suggested that problem-solving counseling may be an effective and culturally acceptable therapeutic tool in the secondary prevention of suicides, which improved coping skills in the target group [ 27 ]. Another pilot has suggested that vendor-based sales restriction in regions with high rates of self-poisoning has the potential to reduce access to pesticides for self-poisoning in the Sri Lankan context [ 28 ].…”
Section: Introductionmentioning
confidence: 99%